1995
DOI: 10.1177/095632029500600206
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antimyxovirus and Anti-Human Immunodeficiency Virus Activities of Polyoxometalates

Abstract: Polyoxometalates have been shown to inhibit the replication of retro-, toga-, paramyxo- and herpesviruses. The primary mechanism of the anti-human immunodeficiency virus type 1 (HIV-1) action of polyoxometalates seems to be inhibition of binding of virus to cells and inhibition of syncytium formation. Since myxoviruses and HIV-1 are known to interact with the cytoplasmic membrane by adsorption and penetration of virus and by fusion of infected and uninfected cells, 25 polyoxometalates were examined for anti-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 20 publications
1
45
1
1
Order By: Relevance
“…The EC so values determined in the present study, albeit with different strains of virus, were significantly higher with this series of POM than with those reported by Shigeta et al (1995). Ikeda et a!.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…The EC so values determined in the present study, albeit with different strains of virus, were significantly higher with this series of POM than with those reported by Shigeta et al (1995). Ikeda et a!.…”
Section: Discussioncontrasting
confidence: 56%
“…Such data suggest these materials to be more selective than expected. Studies using HIV-1 have shown that these large and negatively charged molecules are active at the cell surface (Inouye et al, 1993;Judd et al, 1994), although certain smaller-sized POM have been shown to readily penetrate cell membranes (Hill et al, 1995). The latter observation suggests possible intracellular roles for the antiviral activity of these materials.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations